2015
DOI: 10.35790/ebm.3.1.2015.6607
|View full text |Cite
|
Sign up to set email alerts
|

Uji Resistensi Bakteri Escherichia Coli Yang Diisolasi Dari Plak Gigi Terhadap Merkuri Dan Antibiotik Kloramfenikol

Abstract: Mercury is a liquid element at room temperature. Some main effects of mercury are dysfunctional of brain, kidneys and lungs, tremor, anxiety or nervous, insomnia, fetal growth restriction, and liver damage in pregnancy. Dental plaque is a soft material that attach on tooth’s surface, dental filling, or calculus. Antibiotic is a chemical substance that has the ability to inhibit the growth and kill microorganisms. Chloramphenicol is a broad-spectrum antibiotic that useful for treatment of a number of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…Chloramphenicol is a broad‐spectrum antibiotic that effectively inhibits the growth of Gram‐positive or Gram‐negative bacteria, as well as anaerobic bacteria. (Dian & Budiarso, 2015). The results of the activity test showed that palm waste extracts generally have excellent antibacterial inhibition potential almost the same as the positive control (Chloramfenikol), which is a very strong category.…”
Section: Discussionmentioning
confidence: 99%
“…Chloramphenicol is a broad‐spectrum antibiotic that effectively inhibits the growth of Gram‐positive or Gram‐negative bacteria, as well as anaerobic bacteria. (Dian & Budiarso, 2015). The results of the activity test showed that palm waste extracts generally have excellent antibacterial inhibition potential almost the same as the positive control (Chloramfenikol), which is a very strong category.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, chloramphenicol is positive control, which is a broad-spectrum antibacterial that inhibits both Gram-positive and Gram-negative. It is bacteriostatic at a low dose and bactericidal at high dose [ 30 ]. DMSO 10% is used because of this solvent's nature to dissolve polar and nonpolar compounds, where with a concentration of 10%, DMSO cannot inhibit cell growth in bacteria [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistensi antibiotik bakteri patogen telah menjadi masalah di seluruh dunia. Terjadinya resistensi antibiotik tersebut disebabkan pemakaian antibiotik yang tidak tepat baik untuk pengobatan pada manusia maupun hewan (Indana and Effendi, 2020). Menurut data statistik, konsumsi antibiotik secara global pada tahun 2000 -2010 meningkat sekitar 36%.…”
Section: Pendahuluanunclassified